Acid Treatment of Titania Pastes to Create Scattering Layers in Dye-Sensitized Solar Cells - Trystan Watson; Cecile Charbonneau; Daniel Bryant; David Worsley (International Journal of Photoenergy)
In dye-sensitized solar cells (DSC) scattering layers are used to increase the path length of light incident on the TiO2 film. This is typically achieved by the deposition of an additional TiO2 layer on top of an existing transparent film and designed to trap light. In this work we show that a simple acid pretreatment can lead to the formation of a scattering “skin” on the surface of a single TiO2 film performing a similar function to a scattering layer without any additional depositions. This is important in increasing manufacturing throughput for DSCs as further TiO2 depositions require additional materials and heat treatment. The pretreatment leads to self-assembly of a scattering layer of TiO2 which covers the surface on short-term immersion (<30 min) and penetrates the bulk layer upon longer immersion. The method has been shown to increase the efficiency of the device by 20%.